Advanced designs of solar desalination systems: A review. (September 2015) - El-Sebaii, A.A.; El-Bialy, E.
Abstract: Solar still is an ideal source of fresh water for both domestic and agricultural aspects. It is one of the most important viable applications of solar energy. The simplest and most proven type of solar stills is the single basin type, but its thermal performance is limited. Many research papers were presented where different methods were performed to improve the productivity of single basin solar stills. In this paper, a review of different designs of solar stills was presented particularly the double, triple and multi-effect solar stills, vertical stills, tubular type solar stills, finned and corrugated stills, and stepped type solar stills. A detailed cost analysis for different configurations was presented. The various parameters affecting the performance of the considered designs of solar stills were outlined. The daily productivity of the double basin solar still is on the average 36% higher than that of the single basin still. The inverted absorber triple basin solar still gives a substantially higher yield than double and single basin inverted absorber solar stills. An optimum area of the vertical still absorber was found to be 3.5 m 2 . From the results obtained for the tubular solar still it was concluded that with cooling air flow, the production increased by about 32.8%, and with cooling water flow, it further increased by about 59% more than the system without cooling. A maximum increase in productivity of about 98% was achieved for stepped solar stills when fins, sponge and pebbles were used. The maximum productivity of stepped solar still was obtained with tray depth and width of 5 and 120 mm, which is about 57.3% higher than that of the conventional still.